Effect of aqueous extract of Date Palm Pollen (DPP) on the sperm characteristic and Serum Testosterone, FSH and LH Values in albino male rats treated with sodium floride - AL-Chalabi, Salah M. M. (The Iraqi Journal of Veterinary Medicine, 2014)
The present study was undertaken to evaluate the effect of aqueous extract of Date Palm Pollen DPP on the testicular function and serum testosterone, FSH and LH hormones value. Thirty five male rats were divided randomly into five equal groups. Group 1: received 0.5 ml of distilled water (control group), group 2: was treated orally 0.250 p.p.m of sodium florid (NaF) (with volume of 0.5 ml / rat), Group 3: was treated with 0.250 p.p.m of NaF and 50 mg/kg. B.W. of DPP extract (0.5ml D.W at), Group 4: was treated with 0.250 p.p.m of NaF and 100 mg/kg. B.W. of DPP extract and Group 5: was treated with 0.250 p.p.m of NaF and 150 mg/kg. B.W. of DPP extract. The results showed significant (P< 0.05) decrease in sperm concentration, motility and significant (P< 0.05) increases in dead and abnormal sperm in the group 2 in comparison to control, while all groups of DPP extract showed significant (P< 0.05) increase in sperm concentration, motility and decrease in dead and abnormal sperm. Maximum effect was observed in animals treated with a dose of 150 mg/kg of DPP extract, also the results revealed significant (P< 0.05) increase in testosterone, FSH and LH hormones in groups treated with DDP in comparison to G1andG2. Male rats received DPP for 50 days showed significant (P< 0.05) increases in body and testes weight as compared to G1andG2. In conclusion the results revealed that the aqueous extract of DPP pollen can be used as a sex enhancer and seems to cure male infertility.